JUMPA Vol.2 No.2 Juni 2015 PENGARUH MAKRO EKONOMI TERHADAP JAKARTA ISLAMIC INDEX MENGGUNAKAN ERROR CORRECTION MODEL: PENGARUH MAKRO EKONOMI TERHADAP JAKARTA ISLAMIC INDEX MENGGUNAKAN ERROR CORRECTION MODEL - Farida Fakultas Ekonomi, Universitas Persada Indonesia Y.A.I; Sarpan Fakultas Ekonomi, Universitas Persada Indonesia Y.A.I; Nurwahyuni Fakultas Ekonomi, Universitas Persada Indonesia Y.A.I (Jurnal Manajemen dan Perbankan (JUMPA), 2015)
This study is to conduct test of the long term equilibrium among macroeconomic variables to Jakarta Islamic Index. This study employs co-integration model and error correction model (ECM). The results of this study use unit roots by using Augmented Dickey Fuller method indicate that original data is non stationary, and stationary at first difference. After conducting causality and co-integration test can be concluded that error correction model need to be done and the result is valid. For the long term equilibrium, Error correction model is more capable in explaining if among macroeconomic variables to Jakarta Islamic Index there is causality relationship and simultaneous significantly.